Detection of PIK3CA mutations, including a novel mutation of V344G in exon 4, in metastatic lung adenocarcinomas: A retrospective study of 115 FNA cases. Issue 7 (23rd March 2016) - Allison, Derek B.; Lilo, Mohammed T.; Geddes, Susan; Pallavajjalla, Aparna; Askin, Frederic; Gabrielson, Edward; Zheng, Gang; Li, Qing Kay
Abstract : BACKGROUND: Phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha ( PIK3CA ) mutations and amplification are detected in 1% of primary lung adenocarcinomas (ADCs) and in 38% of primary lung squamous cell carcinomas. Alterations of PIK3CA in metastatic non–small cell lung carcinoma (NSCLC), however, are still not fully understood. This study investigated PIK3CA alterations in metastatic ADCs and correlated the findings with those for other commonly tested molecular abnormalities via fine‐needle aspiration (FNA) and small‐core biopsy materials. METHODS: This study identified 115 FNA cases of metastatic lung ADC with standard lung cancer panel analysis by targeted next‐generation sequencing and fluorescence in situ hybridization at the Johns Hopkins Medical Institute over a 12‐month period. The panel included mutational analysis of PIK3CA, AKT, BRAF, EGFR, ERBB2, KRAS, and NRAS genes and tests of rearrangements for ALK and ROS1 genes. RESULTS: A PIK3CA mutation was detected in 7 of 115 cases of metastatic ADC (6.1%). The majority of the mutations were located in exon 9 or exon 20; however, a mutation in exon 1 was seen in 1 case. Furthermore, p.V344G in exon 4 was detected in 2 cases. Among cases with PIK3CA mutations, 4 had coexisting EGFR mutations, whereas 2 had a coexisting BRAF or KRAS mutation. CONCLUSIONS: Several common mutations as well as a novel mutation in the PIK3CA gene were observed in metastatic NSCLC (particularly ADC). The unique role, however, of PIK3CA mutations in metastatic NSCLC and the clinical implications need to be further investigated. Cancer Cytopathol 2016;124:485–92 . © 2016 American Cancer Society . Abstract : Phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha (P1K3CA) mutation is detected in 7 of 115 cases of metastatic adenocarcinoma (6.1%). Interestingly, a novel mutation for non–small cell lung carcinoma, p.V344G in exon 4, is detected in 2 cases.